Hieracium pallidum subsp. amiatae (Asteraceae), a new subspecis from Monte Amiata (Tuscany, Italy) - Gottschlich, Günter; Selvi, Federico; Dunkel, Franz G. (Phytotaxa, 2024)
Hieracium pallidum subsp. amiatae, a new hawkweed from the summit of the volcanic dome of Monte Amiata (Tuscany, Italy) is described and illustrated. It is similar to H. pallidum subsp. lanudae from which it differs in very dense stellate hairs on the involucral bracts.